PERILAKU OPORTUNISTIK DALAM HUBUNGAN KEMITRAAN (PARTNERSHIP): SEBUAH ANALISIS KONSEPTUAL DENGAN MENGGUNAKAN MODEL IGMOB - Alexander Joseph Ibnu Wibowo (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
This paper reviews the impact of opportunistic behavior in a partnership or the buyer-seller relationship. This study strives to present an integrated general model of opportunistic behavior (IGMOB) to provide a conceptual understanding of opportunistic behavior from the perspective of relationship marketing theory. Various scientific articles from leading journals were re-examined, in particular articles discuss opportunistic behavior. In particular, the causes and consequences of opportunistic behavior were identified, then analyzed their relationships with performance. Based on previous empirical studies, a conceptual understanding was constructed by inserting various relationships among important concepts related. In the context of the relationships between the partners, various studies found that opportunistic behavior has a negative trait for a relationship. There are fifteen factors causing the emergence of opportunistic behavior were identified in this study: temporary relationships (temporality), cultural similarity, formalization, governance, equity-based cooperation, mutual influence, atmosphere of tolerance, mutual respect, satisfaction, length of relationship, flattery, cynicism, deceitful tendencies, and relativity. The study also identified six factors that could be affected by this opportunistic behavior: trust, commitment, cooperation, intention to extent the relationship, knowledge sharing, and guanxi. This study seeks to understand conceptually about the causes and effects of opportunistic behavior in building long-term partnerships between the partners based on a review of current literature. The conceptual model is successfully constructed in this study should be reviewed through various empirical studies.